Education Policy for Globalization: the Malaysian Experiences - Puteh, Alis; Johari, Ahmad Zaidi; Meerah, Subhan M. (European Journal of Social Science Education and Research, 2022)
Phillipson (1998) argued that "globalization policies serve to ensure that the role of English is maintained and perpetuated. The key player in educational policy is the World Bank." Mazrui (1997) said "the World Bank’s real position...encourages the consolidation of the imperial languages in Africa. Its strategies for stabilising and revitalising universities absolutely do not mention of the place of language at tertiary level of African education." According to Stiglitz (2002), "the IMF, the World Bank and the WTO were the three main institutions that govern globalization....they also have been at the centre of the major economic issues for the last two decades". According to Coulmas (1992), the spread of English is linked to modernisation in two ways. Firstly, English is seen as a central tool by which the process of modernisation (globalization) can be achieved particularly in developing societies. Secondly, monolingualism (English) is seen as a practical advantage for modern societies while multilingualism is viewed as a characteristic of traditional societies. The main issue in language policy in any country, especially those categorised as third world countries, is whether the policy is formed according to the agenda of the normal populace or the trans-national corporations. Spring, (1998) argued that "in this scenario elites need to be proficient in English in order to serve their own and global interest, and local languages must facilitate internal policing of an export – oriented economy and attempt to limit social unrest so that this economy can persist. Trans-national corporations are increasingly active in determining the content of education worldwide." Stiglitz (2002) also claimed that "globalization is powerfully driven by international corporations." This development illustrates how the needs and will of these trans-national corporations give rise to producing customer-like citizens more than critical citizens.